Investigating the effect of pcl concentrations on the characterization of pla polymeric blends for biomaterial applications - Solechan, Solechan; Suprihanto, Agus; Widyanto, Susilo Adi; Triyono, Joko; Fitriyana, Deni Fajar; Siregar, Januar Parlaungan; Cionita, Tezara (MDPI, 2022)
Polylactic acid (PLA) and polycaprolactone (PCL) are synthetic polymers that are extensively used in biomedical applications. However, the PLA/PCL blend produced by ball milling, followed by pressure compaction and sintering, has not been extensively explored. The goal of this research is to investigate the effect of the composition of biomaterials derived from PLA and PCL prepared by ball milling, followed by pressure compaction and sintering, on mechanical and physical properties. PCL and PLA with various concentrations were blended utilizing a ball milling machine for 2 h at an 80-rpm rotation speed. The obtained mixture was placed in a stainless steel 304 mold for the compacting process, which uses a pressure of 30 MPa to create a green body. The sintering procedure was carried out on the green body created at 150 °C for 2 h using a digital oven. The obtained PLA/PCL blend was tested using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Scanning electron microscopy (SEM), density, porosity, and three-point bending. Following the interaction between PCL and PLA in the PLA/PCL blend, the FTIR spectra and XRD diffractograms obtained in this work revealed a number of modifications in the functional groups and crystal phase. The 90PLA specimen had the best mechanical properties, with a maximum force and displacement of 51.13 N and 7.21 mm, respectively. The porosity of the PLA/PCL blend decreased with increasing PLA concentration so that the density and flexural properties of the PLA/PCL blend increased. The higher PCL content decreased the stiffness of the PLA molecular chain, consequently reducing its flexural properties.